Valorization of Post-Consumer Recycled Polypropylene Through Their Reinforcement with Amine and Amine/Silane Organically Modified Clays for Potential Use in Food Packaging - Guarda-Moraga, A; Valenzuela-Bascunan, X; Galotto-Lopez, M; Garrido-Ayala, L; Velasquez, E (Elsevier Ltd, 2023)
The deterioration of the properties of post-consumer recycled polyolefins is one of the challenges to address for their further use in new packaging systems. In this work, sheets based on nanocomposites of flexible post-consumer recycled polypropylene (PCPP) and amine (NI44P) and amine/silane (NI.31PS) organic-modified clays were developed in order to study the effect of these nanoclays in the improvement of the PCPP s properties for food packaging applications. Clays tended to reduce the water vapor permeability of the sheets, and interestingly, this effect was more significant by the presence of aminopropyltriethoxysilane as a coupling agent in the clay due to its possible interactions with the oxidized groups of the recycled polymer. Conversely, oxygen permeability increased with NI.31PS clay, but was greatly reduced with the addition of NI.44P at 1 wt%. The nanocomposite with NI.31PS at 3 wt% presented the highest increase of tensile strength. The nanocomposites complied with the overall migration limit towards aqueous and fatty simulants. Migration values were lower in 10 % ethanol and 3 % acetic acid than in olive oil. © 2023 Elsevier Ltd